Case report: Aplastic anaemia and gray matter heterotopias in an autopsy of a 17-year-old puerperal woman - Starosta, Rodrigo Tzovenos; Estivallet, Carmen Liane Neubarth; Schaefer, Pedro Guilherme; De Oliveira, Francine Hehn; Cerski, Marcelle Reesink (Clinical and Biomedical Research, 2016)
In this report, we present an autopsy case of a 17-year-old girl with aplastic anaemia in the puerperal context, along with the presence of four independent nodular gray matter heterotopias in brain slices. The case is remarkable both by the rareness of the cause of death – septicaemia resulting from immunodepression due to aplastic anaemia in the obstetric context – and the brain morphologic findings unrelated to any known clinical manifestation. Immunohistochemistry was performed in order to ensure the precision of the diagnoses.